Experimental Methods in Cryogenic Spectroscopy: Stark Effect Measurements in Substituted Myoglobin - (:unkn) unknown (My University, 2016)
Dawning from well-defined tertiary structure, the active regions of enzymatic proteins exist as specifically tailored electrostatic microenvironments capable of facilitating chemical interaction. The specific influence these charge distributions have on ligand binding dynamics, and their impact on specificity, reactivity, and biological functionality, have yet to be fully understood. A quantitative determination of these intrinsic fields would offer insight towards the mechanistic aspects of protein functionality. This work seeks to investigate the internal molecular electric fields that are present at the oxygen binding site of myoglobin. Experiments are performed at 1 K on samples located within a glassy matrix, using the high-resolution technique spectral hole-burning. The internal electric field distributions can be explored by implementing a unique mathematical treatment for analyzing the effect that externally applied electric fields have on the spectral hole profiles. Precise control of the light field, the temperature, and the externally applied electric field at the site of the sample is crucial. Experimentally, the functionality of custom cryogenic temperature confocal scanning microscope was extended to allow for collection of imaging and spectral data with the ability to modulate the polarization of the light at the sample. Operation of the instrumentation was integrated into a platform allowing for seamless execution of input commands with high temporal inter-instrument resolution for collection of data streams. For the regulated control and cycling of the sample temperature. the thermal characteristics of the research Dewar were theoretically modeled to systematically predict heat flows throughout the system. A high voltage feedthrough for delivering voltages of up to 5000 V to the sample as positioned within the Dewar was developed. The burning of spectral holes with this particular experimental setup is highly repeatable. The quantum mechanical treatment that is employed during analysis of the experimental data requires the state energies and the transition dipole moments of the porphyrin probe. The configuration interaction, as well as the coupled-cluster approaches, have been investigated for their ability to produce realistic valuations for these calculated quantities as gauged by their ability to accurately reproduce valuations for spectroscopically observable transition energies. A capacitive cell, for the determination of a material’s dielectric permittivity, necessary for defining the magnitude of the externally applied electric field at the sample, was developed and shown to successfully yield permittivity valuations for various media in accordance with those reported the literature, while offering the ability to provide measures for permittivities over the temperature range of 1-300 K.
Keywords: Capacitance; Computational Chemistry; Heat Transfer; Microscopy; Spectroccopy